Brief history of arrhythmia in the WPW syndrome – the contribution of George Ralph Mines - Boukens, Bas J (Blackwell Science Inc, 2013)
George Ralph Mines studied the basic principles of reentry and published his data in The Journal of Physiology in 1913. Exactly 100 years later we discuss his first electrophysiological experiments and how his results lead to the insight that was the basis for the treatment of the clinical arrhythmias seen in Wolff–Parkinson–White syndrome.